Oh, the lavas that flow! - Tarpley, Todd; Mathieu, Joe 1949-; Ruiz, Aristides (New York Random House, 2021)
"The Cat in the Hat explains the science behind volcanic eruptions and takes readers on a tour of the most famous volcanoes on Earth-and beyond!"--
"All about volanoes"--Cover
Science (Nature)
Includes bibliographical references (page 43) and index
Ages 5-8
Keywords: Volcanic eruptions -- Juvenile literature; Volcanoes -- Juvenile literature